Relapsed Acute Lymphoblastic Leukemia Presenting as Acute Renal Failure - Rose, Ashley (Case Rep Nephrol, 2019)
Acute lymphoblastic leukemia (ALL) is the second most common acute leukemia in adults. It is an aggressive hematologic neoplasm, with a bimodal age distribution typically presenting in childhood and the 6(th) decade of life (Terwilliger and Abdul-Hay, 2017). Renal injury in ALL is common and can occur through many different mechanisms, such as prerenal acute kidney injury, acute tubular necrosis, renovascular disease, obstruction, glomerulonephritis, and parenchymal infiltration of tumor cells (Luciano and Brewster, 2014). Infiltration of kidneys by leukemia cells is common; however a resultant injury only occurs in about 1% of patients, and renal failure is even more rare (Luciano and Brewster, 2014). Renal failure due to bilateral infiltration of tumor cells has been reported in only a few cases and is thought to be a poor prognostic indicator (Luciano and Brewster, 2014; Sherief et al., 2015). Biopsy is essential to the diagnosis of renal infiltration of leukemia. We present a case of acute renal failure secondary to bilateral renal infiltration of ALL presenting as the first sign of relapse in a young man.